Predictors of survival in surgically treated patients of spinal metastasis - Padalkar, Pravin (Medknow Publications Pvt Ltd, 2011)
BACKGROUND: The spinal metastasis occurs in up to 40% of cancer patient. We compared the Tokuhashi and Tomita scoring systems, two commonly used scoring systems for prognosis in spinal metastases. We also assessed the different variables separately with respect to their value in predicting postsurgical life expectancy. Finally, we suggest criteria for selecting patients for surgery based on the postoperative survival pattern. MATERIALS AND METHODS: We retrospectively analyzed 102 patients who had been operated for metastatic disease of the spine. Predictive scoring was done according to the scoring systems proposed by Tokuhashi and Tomita. Overall survival was assessed using Kaplan–Meier survival analysis. Using the log rank test and Cox regression model we assessed the value of the individual components of each scoring system for predicting survival in these patients. RESULT: The factors that were most significantly associated with survival were the general condition score (Karnofsky Performance Scale) (P=.000, log rank test), metastasis to internal organs (P=.0002 log rank test), and number of extraspinal bone metastases (P=.0058). Type of primary tumor was not found to be significantly associated with survival according to the revised Tokuhashi scoring system (P=.9131, log rank test). Stepwise logistic regression revealed that the Tomita score correlated more closely with survival than the Tokuhashi score. CONCLUSION: The patient's performance status, extent of visceral metastasis, and extent of bone metastases are significant predictors of survival in patients with metastatic disease. Both revised Tokuhashi and Tomita scores were significantly correlated with survival. A revised Tokuhashi score of 7 or more and a Tomita score of 6 or less indicated >50% chance of surviving 6 months postoperatively. We recommend that the Tomita score be used for prognostication in patients who are contemplating surgery, as it is simpler to score and has a higher strength of correlation with survival than the Tokuhashi score.